4CPS-022 High input in patient safety – documentation of cardiovascular system drugs. (March 2019) - Laszloffy, B; Haider, D
Abstract : Background: Cardiovascular disease (CVD), together with its main components, coronary heart disease (CHD), and cerebrovascular diseases, is the main source of morbidity and mortality in the European Union. The involvement of pharmacists demonstrated an ability to improve CVD outcomes through providing education, medicine management or a combination of both. Purpose: To show which areas of CVD could be improved by pharmacists a retrospective analysis of data collection was conducted. Data were derived from a detailed documentation system from 2015 to 2018. Material and methods: Four times a week one pharmacist counselled two wards of a medical department with infectious diseases and tropical medicines with ∼1600 admissions per year. The focus was on CVD drugs according to recent ESC guidelines. Either written recommendations or collaborative agreements with individual physicians were done. Results: One-thousand three-hundred interventions were documented by only one pharmacist. The majority (64%) of these interventions were accepted and implemented. The most common drug classes involved in interventions were CVD drugs (27%) and the most detected drug-related problems (32%) were missing indications. Thirty-one per cent of all CVD drug recommendations concerned stopping nicorandil and NO-donors for missing indication. On the other hand, 45% of all patients who should be on a statin, did not get therapy while hospitalised, if the pharmacists would not have intervened. Fifty-four per cent of recommendations concerned change of medication due to a better side effect profile: diuretics (electrolyte imbalances), ß-Blockers (selectivity) and calcium channel blocker (less flush and oedema). Time of administration for amlodipin and carvedilol was optimised in 70% of cases, and in 21% doses of ACE inhibitors and sartanes according to blood pressure was adapted. Conclusion: Through data analysis the effectiveness of clinical pharmacist interventions within a multidisciplinary team was demonstrated. These error mitigation efforts can serve as a priority in patient safety strategies in this high-risk patient group. These improvements may also lead to an improvement in patients' quality of life, better use of healthcare resources and a reduced rate of mortality. References and/or acknowledgements: Link: The role of the clinical pharmacist in the care of patients with cardiovascular disease. https://www.ncbi.nlm.nih.gov/pubmed/26541925 Acknowledgement: The author thanks the staff of the pharmacy department and hospital for support. No conflict of interest.